Skenario Lahan Pertanian Terlantar di Kabupaten Karawang - Arief Samad; Widiatmaka; Irman Hermadi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
The land plays a significant role in world life to continue its journey and fulfill living things’ needs. However, there is a noticeable increasing trend in farmland abandonment, directly affecting farmers’ livelihood and food security (Paudel et al. 2020). Remote sensing analysis reported that all the districts and subdistricts in Karawang Regency have abandoned land with varying numbers and more distributed more intensely in the hub of the region. The study has discovered that the total number of farmland abandonment is 28 times of the Central Beauaru Statistics has claimed. 75% producer accuracy, terminology, minimum unit data collected, land ownership, and the ability of remote sensing to read all earth reflectan are the possible answer to the disparity. Machine learning informed that the top three essential variables are the irrigation service, the hillside, and the spatial plan that drives farmland abandonment. Thus, developing a new irrigation service to access the remote farmland and reviewing the spatial that have more flavor to the agriculture are the scenario proposed by this study, while the hillside remains a constraint.